THE IMPACT OF REGIONAL TOURISM DEVELOPMENT ON THE FOOD TOURISM INDUSTRY: CASE STUDY OF TOURISM VILLAGE ASSISTANCE POLICY IN INDONESIA AND THE INFLUENCE OF REGIONAL DISPARITY ON ITS EFFECTIVENESS - Rozdianda, Uliannisa; Gultom, Yohanna M. L. (International Review of Humanities Studies, 2024)
This study aims to identify the impact of the development of tourist areas on culinary businesses by taking the case of the program for the construction of facilities and infrastructure supporting tourism villages which was implemented starting in 2017 and looking at the influence of regional disparities on the effectiveness of assistance which is then compared between the regions of Java-Bali and outside Java-Bali. Using the Difference-In-Differences (DID), the study analyzed the impact of the support program on 115 tourism villages, comparing them to other tourism villages in the same sub-district that did not receive support. The results show that, on average, the number of culinary enterprises in the form of restaurants and food stalls in the Java-Bali region increased by 12 units after the implementation of the Tourism Village Programme, in contrast to Tourism Villages in the same sub-district that did not receive support. These findings are supported by the better condition of road infrastructure, street lighting, and telephone signals in Tourism Villages in Java and Bali. The results of this study explain that regional disparities have an impact on the growth of culinary enterprises in tourism villages.